Spontaneously Regenerative Tough Hydrogels. Issue 32 (1st July 2019) - Qu, Gang; Li, Yang; Yu, Yafeng; Huang, Yuxing; Zhang, Wei; Zhang, Han; Liu, Zhou; Kong, Tiantian
Abstract: Sponges, Neofibularia nolitangere, can regenerate spontaneously after being broken down into small pieces, and the regenerated structure maintains the original appearance and function. Synthetic materials with such capabilities are highly desired but hardly achieved. Presented here is a sponge‐inspired self‐regenerative powder from a double‐network (DN) tough hydrogel. Hydrogels are regenerated from their powder form, by addition of water, with preservation of the original appearance and mechanical properties. The powder‐hydrogel‐powder cycle can be repeated multiple times with little loss in mechanical properties, analogous to the regeneration of sponges. These DN hydrogels can be conveniently stored and easily shaped upon regeneration. This work may have implications in the development of regenerative materials for coatings and adhesives. Abstract : Self‐healing : A sponge‐inspired self‐regenerative double‐network hydrogel that can spontaneously regenerate from its dry powder form has been developed. The powders can be restored to hydrogels having the original appearance and super‐stretchability. They can also be stored for a long time without loss in the regenerative capacity. The powder‐to‐hydrogel transformation provides unprecedented convenience for the purposes of storage as well as the shaping of tough hydrogel‐based materials.